Entre démocratisation et professionnalisation: le Parlement suisse et ses membres de 1910 à 2016 - Pilotti, Andrea (Seismo, 2016)
This book provides a detailed historical analysis of the Swiss Parliament. It sheds light on how the profiles of parliamentarians have evolved over a century, and recounts the various legislative reforms affecting their status. The author analyses the impact of these reforms on the collective biography of the members of Parliament. The rich data allow for an empirically grounded reflection on how well the parliamentary composition represents the population, for instance in terms of their gender or level of education, and an understanding of the processes of democratization and professionalization of the institution. This research has received a prize from the Faculty of Social and Political Sciences at the University of Lausanne and an incentive award from the Swiss Society for Parliamentary Questions. Andrea Pilotti has a PhD in Political Sciences from the University of Lausanne. He is Research Manager at the Research Observatory for Regional Politics and member of the Swiss Elite Observatory at the University of Lausanne's Faculty of Social and Political sciences.